Representación de la protesta social en las movilizaciones ciudadanas en el Perú durante el periodo pre- y poselectoral de 2021: análisis desde la visualidad de un trabajo fotográfico - Velarde Castillo, Jackeline Sofía (2022)
Aldair Mejía is a Peruvian photographer who became moderately well known in the outbreak of social protest in Peru during November 2020. His work has recorded the citizen mobilizations in the country before, during and after the last presidential elections of 2021, that gave Pedro Castillo as the winner. The subject of this article has to do with, from the visuality, exploring and describing the representation of the social claim in this photographic work, using three photographs as the object of analysis. The methodology of visual analysis has been specifically used and it is not intended to generalize the meaning and implication of the images in other contexts. The focus has been on defining what kind of visual discourse these images constitute in the context of the enunciation and repetition of messages, mostly contrary, by the media, economic powers and defenders of the status quo, in the context of the political tension between candidates and what their figures represented until the announcement of the official winner.